An Evaluation of the Implementation of the Village Financial System (SISKEUDES) and Its Effect on the Effectiveness of Budget Realization Reporting in Puntang Village - Hotang, Keri Boru; Klara, Iis (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2025)
SISKEUDES application is a financial management system application designed by the Ministry of Home Affairs together with the Financial and Development Supervisory Agency in accordance with the Regulation of the Minister of Home Affairs (Permendagri) No. 20 of 2018 concerning Village Financial Management Launching of Siskeudes version 2.0. This digital innovation is useful to facilitate the performance of village officials in the process of reporting the realization of the Puntang Village government budget in Palembang City. However, in its use, this SISKEUDES application is still a challenge for Puntang Village officials, Empat Lawang Regency, Palembang City. Furthermore, the purpose of this study is to describe the implementation of the use of the SISKEUDES application in Puntang Village, Palembang City. In analyzing, researchers use the Policy Implementation theory from Charles O. Jones to be able to explain more details regarding this problem. This study uses a qualitative case study method, as well as in-depth interviews with key informants, namely; Village Head; Head of Village Planning; and Head of Village Finance. The results of this study indicate that (1) Lack of readiness of human resources in the organization in Puntang Village, Palembang City; (2) The implementation of the SISKEUDES application in Puntang Village, Palembang City, is still often hampered by technical issues. Thus, the implementation of the SISKEUDES application cannot yet be said to be effective. This research is expected to be used as material for re-evaluation in the implementation of digital-based financial management in each village.